Pros and Cons - Beatty, David (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1975)
In this paper, the author concludes that the collective bargaining model will be able to preserve the most vital features of the intellectual community.